Distinct patterns of hepcidin and iron regulation during HIV-1, HBV, and HCV infections. - Armitage, A; Stacey, A; Giannoulatou, E; Marshall, E; Sturges, P; Chatha, K; Smith, N; Huang, X; Xu, X; Pasricha, SR; Li, N; Wu, H; et al. (National Academy of Sciences, 2014)
During HIV type-1 (HIV-1), hepatitis C virus (HCV), and hepatitis B virus (HBV) infections, altered iron balance correlates with morbidity. The liver-produced hormone hepcidin dictates systemic iron homeostasis. We measured hepcidin, iron parameters, cytokines, and inflammatory markers in three cohorts: plasma donors who developed acute HIV-1, HBV, or HCV viremia during the course of donations; HIV-1-positive individuals progressing from early to chronic infection; and chronically HIV-1-infected individuals (receiving antiretroviral therapy or untreated). Hepcidin increased and plasma iron decreased during acute HIV-1 infection, as viremia was initially detected. In patients transitioning from early to chronic HIV-1 infection, hepcidin in the first 60 d of infection positively correlated with the later plasma viral load set-point. Hepcidin remained elevated in individuals with untreated chronic HIV-1 infection and in subjects on ART. In contrast to HIV-1, there was no evidence of hepcidin up-regulation or hypoferremia during the primary viremic phases of HCV or HBV infection; serum iron marginally increased during acute HBV infection. In conclusion, hepcidin induction is part of the pathogenically important systemic inflammatory cascade triggered during HIV-1 infection and may contribute to the establishment and maintenance of viral set-point, which is a strong predictor of progression to AIDS and death. However, distinct patterns of hepcidin and iron regulation occur during different viral infections that have particular tissue tropisms and elicit different systemic inflammatory responses. The hypoferremia of acute infection is therefore a pathogen-specific, not universal, phenomenon.